SUSTAINABLE IMPLEMENTATION OF PUBLIC RESOURCES IN SUPPORT OF ECONOMIC AND SOCIAL RECONSTRUCTION - Hiskia C.M Sapioper (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
Sustainable economic and social development in line with general well-being depends heavily on the effective and efficient management of public finances. The study aims to investigate how careful management of public financial resources can help drive social and economic progress in various sectors. The research uses a literary research approach, in which information is collected from a variety of existing sources, including scientific journals, government reports, publications of international organizations, and other academic literature relevant to public finance management topics. The results of this study show that proper public finance management, which includes transparency, accountability, optimization of state receipts, efficient spending management, a performance-based budgeting approach, careful debt management, and active participation of various stakeholders, have a significant impact in supporting long-term development goals.